Growth variation and heritability in a second-generation Eucalyptus urophylla progeny test at Lad Krating Plantation, Chachoengsao province, Thailand - Dlamini, Lucky Nhlanhla; Pipatwattanakul, Damrong; Maelim, Somporn (Agriculture and Natural Resources, 2017)
In Thailand, Eucalyptus urophylla was introduced with the main purpose of supplying raw material for pulp and chip wood production. The demand for genetically improved seed is increasing to support high productivity plantation establishment. One of the tree improvement activities established to meet the high demand for improved seed was a second generation progeny test at Lad Krating Plantation, Thailand to provide the best material for the successful plantation program. The aim of the current study was to compare growth variation of the first and second generation of Eucalyptus urophylla progeny that could provide information on suitable families for improved quality seed. The progeny test comprised the best 45 half-sib families selected from 80 half-sib families of the first-generation progeny test. The design of the progeny test was a randomized and complete block design (16 trees/plot x 45 plots/block x 9 blocks), with 4 rows of 4 trees at a spacing of 2 m x 1 m. Growth was assessed at age 3 yr. The average height and diameter at breast height over bark (DBH), was 13.72 m, and 8.75 cm, respectively. There were highly significant (p < 0.01) differences among provenances and families in both height and DBH. The individual heritability values for height and DBH were 0.48 and 0.60, respectively. The family heritability values for height and DBH were 0.98 and 0.99, respectively. These 45 half-sib families proved to be genetically superior ensuring higher productivity and contributing to the success of the Forest Industry Organization plantation at Lad Krating.